2010
DOI: 10.1088/0004-637x/712/1/350
|View full text |Cite
|
Sign up to set email alerts
|

THE RISE AND FALL OF TYPE Ia SUPERNOVA LIGHT CURVES IN THE SDSS-II SUPERNOVA SURVEY

Abstract: We analyze the rise and fall times of type Ia supernova (SN Ia) light curves discovered by the Sloan Digital Sky Survey-II (SDSS-II) Supernova Survey. From a set of 391 light

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
133
5
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(161 citation statements)
references
References 93 publications
22
133
5
1
Order By: Relevance
“…They found that the SN extinction, which is proportional to the mean column density over the photodisk, would likely vary with time by a substantial amount over a period spanning 140 days from the time of explosion. Their Figure 8 showed especially dramatic variations within 60 days after explosion, corresponding to a phase of approximately 43 days (e.g., Hayden et al 2010). This is the period when most light curve measurements for cosmology applications are made.…”
Section: Summary Of Relevant Results In P10 and F13mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the SN extinction, which is proportional to the mean column density over the photodisk, would likely vary with time by a substantial amount over a period spanning 140 days from the time of explosion. Their Figure 8 showed especially dramatic variations within 60 days after explosion, corresponding to a phase of approximately 43 days (e.g., Hayden et al 2010). This is the period when most light curve measurements for cosmology applications are made.…”
Section: Summary Of Relevant Results In P10 and F13mentioning
confidence: 99%
“…Finally, it is instructive to see how the extinction fluctuation RMS depends on the phase. Employing the equation for the diameter of the photodisk t days after explosion given by P10, in terms of the phase T (= t + 17.4; e.g., Hayden et al 2010), for γ = −2.9, we can write: …”
Section: Normalization For Extinction Fluctuationsmentioning
confidence: 99%
“…Thus, the B-band maximum occured ∼17.2 days after explosion, very similar to the value derived by Foley et al (2012a) for SN 2009ig (17.13 days), which was also discovered in less than a day after explosion. The average value for the majority of "normal" SNe Ia is ∼17.4 ± 0.2 days (Hayden et al 2010). This supports the conclusion from spectroscopy that SN 2011fe is a "normal" SN Ia.…”
Section: Constraining the Moment Of Explosion And B-band Maximummentioning
confidence: 98%
“…The light curves evolve very slowly. For SN 2009dc, Silverman et al (2011 reported a first detection on an image taken 21 d before B-band maximum, and estimated a rise time of 23 ± 2 d, significantly longer than in normal SNe Ia (17-20 d; Conley et al 2006;Hayden et al 2010). Also the decline rates after peak are among the slowest ever observed for SNe Ia, with ∆ m 15 (B) between 0.7 and 0.9.…”
Section: Early-time Light Curves and Peak Luminositymentioning
confidence: 98%